Tecnologias de informação e comunicação (tics) aliadas às práticas pedagógicas: um estudo em escolas de ensino médio de Araguaína - TO - Oliveira, Fabiana Valeriana (Universidade Federal do Tocantins, 2022)
This work seeks to reflect upon how information and communication technologies (ICTs ) are used in the teaching- learning process in high schools in the city of Araguaína - TO . It wanted to discuss the teachers' position of some schools surveyed through a questionnaire. Firstly, we did a literature review of relevant concepts for the understanding of the subject. Secondly, it was exposed what I found in the field research in relation to bibliographic references. It is understood, in general way, that the subject of this work is of great importance and addresses something that tends to settle into the school environment. Making it necessary for the teachers to adapt and interact with ICTs . Among the results of this research I see the lack of continuous training for teachers to work with ICT in the school environment and an not effective and everyday use of ICT within the classroom.